The influence of village fund capital participation in Village-Owned Enterprises on the development of Village-Owned Enterprises and the economy of the Wania District community - Sisilia T Kristiyani; Elsyan R Marlissa; Transna Putra Urip (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of village fund capital participation on the development of Village-Owned Enterprises (BUMKam) and its impact on the economic improvement of the community in Wania District, Papua. It seeks to understand how financial support from village funds contributes to the sustainability of BUMKam operations and local economic growth. Research/methodology: A quantitative descriptive method was applied using questionnaires, observations, and documentation. The sample consisted of 13 respondents, including BUMKam administrators and community members, selected purposively. Data analysis compared pre- and post-capital injection conditions, emphasizing enterprise growth, job creation, and welfare improvement. Results: The findings show that capital participation from village funds has positively influenced the growth of BUMKam in Kampung Mawokauw Jaya and Kampung Nawaripi. It enabled the establishment of several productive units and provided job opportunities, contributing to increased local income and economic activity. However, challenges remain, particularly in financial reporting and management capacity among BUMKam administrators. Conclusions: While the injection of capital has facilitated enterprise growth and modest improvements in local welfare, the full potential of BUMKam is hindered by gaps in administrative skills and community engagement. Sustainable impact requires capacity building, transparent governance, and strategic support. Limitations: The study’s small sample size and reliance on descriptive analysis limit broader generalization and causal conclusions. Contribution: This study provides preliminary evidence of the positive impact of Village Fund capital participation on Village-Owned Enterprises (BUMKam) and the local economy, while offering practical insights for more effective village fund management.